Sikap Mahasiswa dalam Adopsi Aplikasi Keuangan BRIMO dengan Pendekatan Technology Acceptance Model (TAM) - Saputra, Moh Sahdan; Nurjihadi, Muhammad (Puslitbang Sinergis Asa Professional, 2023)
This study aims to investigate the attitudes of university students towards the adoption of the BRIMO financial application using the Technology Acceptance Model (TAM) approach. The research employed a quantitative survey-based methodology, with the target population consisting of students who are users of the BRIMO application. The research sample comprised more than 100 respondents selected through convenience sampling. The questionnaire was developed based on relevant previous research, and data were collected using a Likert scale with 4 categories. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings of the study revealed that the perceived ease of use has a significant positive impact on the usage attitude towards the BRIMO application among students. However, the perceived usefulness was not found to have a significant influence on the usage attitude. Additionally, the perceived ease of use was also found to have a significant positive effect on the perceived usefulness, with the perceived usefulness acting as a mediating variable between the perceived ease of use and the usage attitude towards the BRIMO application among students.